Crosslinked polyethylene material for high-voltage direct-current cable and preparation method of crosslinked polyethylene material

Through the combination of gradient crosslinking and specific nanomaterials, a stable three-dimensional crosslinking network is formed, which solves the problem of easy insulation aging of crosslinked polyethylene materials and improves the insulation performance and thermal stability of high-voltage DC cables.

CN120574464AActive Publication Date: 2025-09-02HUNAN YIYUANXIN TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510759562.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-09-02
Estimated Expiration
2045-06-09

AI Technical Summary

Technical Problem

The existing crosslinked polyethylene materials are prone to insulation and aging, which limits the development of high-voltage DC cables to higher voltage levels.

Method used

By mixing modified polyethylene, linear low-density polyethylene, modified titanium dioxide, block copolymer, modified alumina, methyl acrylate, diapropyl peroxide, antioxidant 1010 and synergist, a stable three-dimensional crosslinking network is formed, and the interface structure is optimized by combining a physical crosslinking network of hexagonal boron nitride nanosheets and graphene oxide in a specific proportion.

Benefits of technology

It significantly improves the insulation aging resistance, thermal stability, insulation and mechanical properties of cross-linked polyethylene materials, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a crosslinked polyethylene material for a high-voltage direct-current cable and a preparation method of the crosslinked polyethylene material, and relates to the technical field of high polymer material processing. The preparation method comprises the following steps: mixing modified polyethylene, linear low-density polyethylene, modified titanium dioxide, a block copolymer, modified aluminum oxide, methyl acrylate, dicumyl peroxide, an antioxidant 1010 and a synergist, carrying out compression molding, carrying out gradient crosslinking in a nitrogen atmosphere, and cooling to obtain the crosslinked polyethylene material for the high-voltage direct-current cable. The modified polyethylene and the linear low-density polyethylene are compounded according to a specific proportion, so that the insulativity and the high-temperature stability of the material are effectively improved; and due to the introduction of the modified titanium dioxide, the block copolymer, the synergist and other components, the insulation aging resistance, the thermal stability, the insulativity and the mechanical property of the material are further improved. Therefore, the method has a wider application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer material processing, and in particular to a cross-linked polyethylene material for high-voltage direct current cables and a preparation method thereof. Background Art

[0002] HVDC cables are used to transmit high-voltage DC power and consist of four components: conductor, insulation, shield, and sheath. Cross-linked polyethylene (XLPE) is widely used as the insulation layer for HVDC cables due to its excellent insulation, electrical resistance, flexibility, tensile strength, tear strength, heat resistance, acid and alkali corrosion resistance, and water resistance. However, issues such as high conductivity-temperature sensitivity, space charge accumulation, and insulation aging have limited the further development of HVDC cables to higher voltage levels.

[0003] In order to suppress the problem of high conductivity-temperature sensitivity of cross-linked polyethylene materials, relevant technicians have conducted numerous studies and proposed solutions such as nanoparticle doping modification and organic molecule grafting. For example, the patent document CN114031837A proposes a cross-linkable polyethylene insulation material for high-voltage cables, a preparation method and its use. According to the mass percentage of each component, the insulation material described in the powder includes the following components: 97.5%-99.3% polyethylene base material, 0.5%-2% cross-linking agent, 0.1%-0.5% co-cross-linking agent and 0.1%-0.5% antioxidant. This invention modifies traditional insulation materials by introducing highly branched polyethylene, reduces the polar cross-linking decomposition byproducts in the insulation material that cause nonlinear changes in conductivity, effectively suppresses the generation and migration of charges under a DC electric field, and thus suppresses the nonlinear effect of conductivity in high-voltage cables.

[0004] However, the problem of easy insulation aging of cross-linked polyethylene materials prepared by these existing methods still needs to be further solved. Summary of the Invention

[0005] The purpose of the present invention is to provide a cross-linked polyethylene material for high-voltage DC cables and a preparation method thereof, to solve the following technical problems: Existing cross-linked polyethylene materials are prone to insulation aging.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a cross-linked polyethylene material for a high-voltage DC cable comprises the following steps: Modified polyethylene, linear low-density polyethylene, modified titanium dioxide, block copolymer, modified aluminum oxide, methyl acrylate, dicumyl peroxide, antioxidant 1010, and synergist are mixed and compression molded, and then gradient cross-linked under a nitrogen atmosphere and cooled to obtain a cross-linked polyethylene material for high-voltage DC cables.

[0007] Preferably, the modified polyethylene, linear low-density polyethylene, modified titanium dioxide, block copolymer, modified aluminum oxide, methyl acrylate, dicumyl peroxide, antioxidant 1010, and synergist are mixed in a ratio of 60-70 g: 30-35 g: 0.5-2 g: 5-6 g: 5-6 g: 3-5 g: 1-2 g: 2-3 g: 1-2 g; The gradient cross-linking comprises first heating to 160-170° C. for cross-linking for 10-15 minutes, then heating to 180-190° C. for cross-linking for 10-15 minutes, and finally heating to 195-205° C. for cross-linking for 10-15 minutes.

[0008] Preferably, the preparation method of the modified polyethylene is as follows: Under a nitrogen atmosphere, low-density polyethylene, maleic anhydride, and dicumyl peroxide are mixed and melt-blended at 180° C. for 20-25 minutes, and then granulated to obtain modified polyethylene; The usage ratio of the low-density polyethylene, maleic anhydride and dicumyl peroxide is 100g:1.5-3g:0.1-0.3g.

[0009] Preferably, the preparation method of the modified titanium dioxide is as follows: The nano-titanium dioxide is dispersed in an ethanol aqueous solution, dopamine hydrochloride is added, ultrasonic treatment is performed, and then centrifugal separation and drying are performed to obtain modified titanium dioxide; The usage ratio of the nano-titanium dioxide, the ethanol aqueous solution and the dopamine hydrochloride is 1-2 g:100 mL:0.05-0.1 g.

[0010] Preferably, the preparation method of the block copolymer is as follows: Step A1: Under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylacetamide were added to 4,4'-oxydiphthalic anhydride in sequence, and the mixture was stirred at 0-5°C for 6-7 hours. Then, acetic anhydride and pyridine were added, and the mixture was heated to 150-180°C and reacted for 5-5.2 hours to obtain a polyimide; Step A2: dissolving polyimide in N,N-dimethylformamide, adding polyethyleneimine and azobisisobutyronitrile, and reacting at 80-90° C. for 7-8 hours to obtain a block copolymer.

[0011] Preferably, the usage ratio of 4,4'-oxydiphthalic anhydride, 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide, acetic anhydride, and pyridine in step A1 is 27-31 g: 17.6-20 g: 200 mL: 15-17 g: 10-11.4 g; The usage ratio of the polyimide, N,N-dimethylformamide, polyethyleneimine, and azobisisobutyronitrile in step A2 is 40-45 g:150 mL:5-5.7 g:0.5-0.57 g.

[0012] Preferably, the preparation method of the modified alumina is as follows: The silane coupling agent KH550 and ethanol are mixed evenly, and then nano-alumina is added and ultrasonically treated at 55-60° C. for 2-3 hours, and then centrifuged and dried to obtain modified alumina.

[0013] Preferably, the usage ratio of the silane coupling agent KH550, ethanol, and nano-alumina is 0.04-0.18 g:100 mL:2-6 g.

[0014] Preferably, the preparation method of the synergist is as follows: Chitosan is dispersed in an acetic acid aqueous solution at 10-20°C, and then hexagonal boron nitride nanosheets, graphene oxide and deionized water are added and ultrasonically dispersed. Sodium lauryl sulfate is then added and bidirectionally frozen into shape. After vacuum freeze-drying, gradient annealing is performed in a nitrogen atmosphere, and the synergist is obtained after cooling.

[0015] Preferably, the chitosan, acetic acid aqueous solution, hexagonal boron nitride nanosheets, graphene oxide, deionized water, and sodium lauryl sulfate are used in a ratio of 30-50 g: 500 mL: 1-2 g: 0.1-0.5 g: 500-600 mL: 0.05-0.1 g; The gradient annealing is performed at 100° C. for 1 h in the first stage annealing, and then at 200-250° C. for 2 h in the second stage annealing.

[0016] Beneficial effects of the present invention: The present invention provides a cross-linked polyethylene material for high-voltage direct current cables and a preparation method thereof. The present invention effectively improves the insulation aging resistance of the cross-linked polyethylene material through the following method.

[0017] (1) The addition of hexagonal boron nitride nanosheets and graphene oxide in a specific proportion in the synergist of the present invention can generate a physical cross-linking network and hydrogen bonding and other interaction forces within the cross-linked polyethylene material and form a network skeleton, thereby effectively hindering the crack propagation path and inhibiting the occurrence of phenomena such as strain concentration, carrier migration and electrical tree induction, thereby improving the tensile strength, fracture toughness and impact resistance of the material while also improving the insulation and thermal stability. The bidirectional freezing-gradient annealing process will form an ordered cross-linked structure and a layered multi-arch structure of the synergist, so that the material can disperse stress through the "arch bridge effect", further improving the mechanical properties and thermal stability of the material. The synergist will also work together with diisopropylbenzene peroxide to form a more stable three-dimensional cross-linked network, further improving the thermal stability of the material.

[0018] (2) The present invention improves the polarity and cross-linking degree of low-density polyethylene by grafting and cross-linking with maleic anhydride, and blending it with linear low-density polyethylene in a specific proportion further enhances the interfacial bonding, balances the toughness and strength, crystallinity and uniformity of the cross-linked polyethylene material, and effectively improves the mechanical properties, structural stability, insulation properties and high-temperature stability of the cross-linked polyethylene material.

[0019] (3) The addition of modified alumina in a specific proportion in the present invention can significantly improve the tensile strength, elastic modulus, and wear resistance of the material, form physical crosslinking points, and inhibit chain segment motion. The addition of modified titanium dioxide can improve toughness through interfacial stress transfer, and the two will form a composite reinforcement network within the material, balancing strength and toughness. At the same time, the addition of both can also promote the occurrence of crosslinking reactions, improve the insulation, thermal conductivity, and thermal stability of the material, and inhibit the growth of electrical dendrites, thereby increasing the breakdown field strength.

[0020] (4) The block copolymer of the present invention can be used as an interfacial compatibilizer to improve the compatibility of modified polyethylene and linear low-density polyethylene, reduce phase separation, and enhance the tensile strength and elongation at break of the material. Its polar groups can also produce surface interactions with nanofillers, promote uniform dispersion of fillers, form stronger interfacial bonding, and thus improve the modulus and toughness of the composite material. The block structure of the block copolymer will inhibit the accumulation of space charges and enhance the insulation properties of the material through the synergistic effect of molecular segments. While the block copolymer inhibits the movement of chain segments at high temperatures, its rigid structure will also work together with diisopropylbenzene peroxide to form a thermally stable three-dimensional network, thereby increasing the thermal decomposition temperature and long-term use temperature of the material. The block copolymer will also combine with the layered structure in the synergist to form a "sandwich" interface, further optimizing impedance matching and interfacial polarization loss, and enhancing the material's corona resistance and breakdown strength.

[0021] Therefore, the cross-linked polyethylene material for high-voltage DC cables prepared by the present invention has more excellent resistance to insulation aging, thermal stability, insulation, mechanical properties, and broad application prospects. DETAILED DESCRIPTION

[0022] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0023] The properties and sources of some raw materials in the present invention are as follows: Low-density polyethylene was purchased from Shanghai Myrrel Biochemical Technology Co., Ltd., CAS: 9002-88-4, product number: M58947; nano-titanium dioxide was purchased from Shanghai Yunfu Nanotechnology Co., Ltd., CAS: 13463-67-6; nano-alumina was purchased from Hubei Xinrunde Chemical Co., Ltd., model: TAP-A20, CAS: 1344-28-1; polyethyleneimine (Mn=20000) was purchased from Suzhou Yake Technology Co., Ltd., CAS: 9002-98-6; linear low-density polyethylene was purchased from Shanghai Myrrel Biochemical Technology Co., Ltd., CAS: 9002-88-4, product number: M85222.

[0024] Example 1: A method for preparing a cross-linked polyethylene material for a high-voltage DC cable is as follows: S1: Under a nitrogen atmosphere, 100 g of low-density polyethylene, 1.5 g of maleic anhydride, and 0.1 g of dicumyl peroxide were mixed and melt-blended at 180°C for 20 min, followed by granulation to obtain modified polyethylene; S2: 1 g of nano-titanium dioxide was dispersed in 100 mL of 20% ethanol aqueous solution, followed by the addition of 0.05 g of dopamine hydrochloride and ultrasonic treatment at a power of 200 W and a frequency of 40 kHz for 30 min. The modified titanium dioxide was then obtained by centrifugation and drying. S3: Under a nitrogen atmosphere, 17.6 g of 4,4'-diaminodiphenyl ether and 200 mL of N,N-dimethylacetamide were added to 27 g of 4,4'-oxydiphthalic anhydride in sequence, and the mixture was stirred at 0°C for 6 h. Then, 15 g of acetic anhydride and 10 g of pyridine were added, and the temperature was raised to 150°C and the reaction was carried out for 5 h to obtain a polyimide; S4: 40 g of polyimide was dissolved in 150 mL of N,N-dimethylformamide, 5 g of polyethyleneimine and 0.5 g of azobisisobutyronitrile were added, and the mixture was reacted at 80°C for 7 h to obtain a block copolymer; S5: 0.04 g of silane coupling agent KH550 was mixed evenly with 100 mL of ethanol, and then 2 g of nano-alumina was added and ultrasonicated at 55°C for 2 h. The mixture was then centrifuged and dried to obtain modified alumina. S6: At 10°C, 30 g of chitosan was dispersed in 500 mL of a 1% acetic acid aqueous solution, followed by the addition of 1 g of hexagonal boron nitride nanosheets, 0.1 g of graphene oxide, and 500 mL of deionized water. The mixture was ultrasonically dispersed at a power of 200 W, a frequency of 40 kHz, and a time of 30 min. 0.05 g of sodium dodecyl sulfate was then added and bidirectionally frozen to form the mixture. The mixture was vacuum freeze-dried and annealed at 100°C for 1 h in a first stage under a nitrogen atmosphere, followed by a second stage annealing at 200°C for 2 h. The synergist was obtained after cooling. S7: 60g of modified polyethylene, 30g of linear low-density polyethylene, 0.5g of modified titanium dioxide, 5g of block copolymer, 2g of modified alumina, 3g of methyl acrylate, 1g of diisopropyl peroxide, 2g of antioxidant 1010, and 1g of enhancer were mixed at 170°C for 15min and then compression molded at 115°C. The mixture was then heated to 160°C under a nitrogen atmosphere for cross-linking for 10min, then heated to 180°C for cross-linking for 10min, and finally heated to 195°C for cross-linking for 10min. After cooling, a cross-linked polyethylene material for high-voltage DC cable was obtained.

[0025] Example 2: A method for preparing a cross-linked polyethylene material for a high-voltage DC cable is as follows: S1: Under a nitrogen atmosphere, 100 g of low-density polyethylene, 2.25 g of maleic anhydride, and 0.2 g of dicumyl peroxide were melt-blended at 180°C for 23 min, and then granulated to obtain modified polyethylene; S2: 1.5 g of nano-titanium dioxide was dispersed in 100 mL of 20% ethanol aqueous solution, followed by the addition of 0.08 g of dopamine hydrochloride and ultrasonic treatment at a power of 250 W and a frequency of 40 kHz for 30 min. The solution was then centrifuged and dried to obtain modified titanium dioxide. S3: Under a nitrogen atmosphere, 18.8 g of 4,4'-diaminodiphenyl ether and 200 mL of N,N-dimethylacetamide were added to 29 g of 4,4'-oxydiphthalic anhydride in sequence, and the mixture was stirred at 3°C ​​for 6.5 h. Then, 16 g of acetic anhydride and 10.7 g of pyridine were added, and the temperature was raised to 165°C and the reaction was continued for 5.1 h to obtain a polyimide; S4: 42.5 g of polyimide was dissolved in 125 mL of N,N-dimethylformamide, 5.3 g of polyethyleneimine and 0.53 g of azobisisobutyronitrile were added, and the mixture was reacted at 85°C for 7.5 h to obtain a block copolymer; S5: 0.11 g of silane coupling agent KH550 was mixed with 100 mL of ethanol, and then 4 g of nano-alumina was added and ultrasonicated at 58°C for 2.5 h. The mixture was then centrifuged and dried to obtain modified alumina. S6: At 15°C, 40g of chitosan was dispersed in 500mL of 1% acetic acid aqueous solution, followed by the addition of 1.5g of hexagonal boron nitride nanosheets, 0.3g of graphene oxide, and 550mL of deionized water. Ultrasonic dispersion was performed at a power of 300W, a frequency of 40kHz, and a time of 45min. 0.08g of sodium lauryl sulfate was then added and bidirectionally frozen to form the mixture. The mixture was vacuum freeze-dried and annealed at 100°C for 1h in a nitrogen atmosphere in the first stage, followed by annealing at 225°C for 2h in the second stage. The synergist was obtained after cooling. S7: 65g of modified polyethylene, 32.5g of linear low-density polyethylene, 1.75g ​​of modified titanium dioxide, 5.5g of block copolymer, 4g of modified alumina, 4g of methyl acrylate, 1.5g of diisopropyl peroxide, 2.5g of antioxidant 1010, and 1.5g of enhancer were mixed at 175°C for 18min and then compression molded at 120°C. The mixture was then heated to 165°C under a nitrogen atmosphere for cross-linking for 13min, then heated to 185°C for cross-linking for 13min, and finally heated to 200°C for cross-linking for 13min. After cooling, a cross-linked polyethylene material for high-voltage DC cable was obtained.

[0026] Example 3: A method for preparing a cross-linked polyethylene material for a high-voltage DC cable is as follows: S1: Under a nitrogen atmosphere, 100 g of low-density polyethylene, 3 g of maleic anhydride, and 0.3 g of dicumyl peroxide were melt-blended at 180°C for 25 min, and then granulated to obtain modified polyethylene; S2: 2 g of nano-titanium dioxide was dispersed in 100 mL of 20% ethanol aqueous solution, followed by the addition of 0.1 g of dopamine hydrochloride and ultrasonic treatment at a power of 300 W and a frequency of 40 kHz for 30 min. The modified titanium dioxide was then obtained by centrifugation and drying. S3: Under a nitrogen atmosphere, 20 g of 4,4'-diaminodiphenyl ether and 200 mL of N,N-dimethylacetamide were added to 31 g of 4,4'-oxydiphthalic anhydride in sequence, and the mixture was stirred at 0-5°C for 7 h. Then, 17 g of acetic anhydride and 11.4 g of pyridine were added, and the temperature was raised to 180°C and the reaction was continued for 5.2 h to obtain a polyimide; S4: 45 g of polyimide was dissolved in 150 mL of N,N-dimethylformamide, 5.7 g of polyethyleneimine and 0.57 g of azobisisobutyronitrile were added, and the mixture was reacted at 90°C for 8 h to obtain a block copolymer; S5: 0.18 g of silane coupling agent KH550 was mixed with 100 mL of ethanol, and then 6 g of nano-alumina was added and ultrasonicated at 60°C for 3 h. The mixture was then centrifuged and dried to obtain modified alumina. S6: At 20°C, 50 g of chitosan was dispersed in 500 mL of 1% acetic acid aqueous solution, followed by the addition of 2 g of hexagonal boron nitride nanosheets, 0.5 g of graphene oxide, and 600 mL of deionized water. Ultrasonic dispersion was performed at a power of 400 W, a frequency of 40 kHz, and a time of 60 min. 0.1 g of sodium dodecyl sulfate was then added and bidirectionally frozen to form the mixture. After vacuum freeze-drying, the mixture was annealed at 100°C for 1 h in a first stage under a nitrogen atmosphere, followed by a second stage annealing at 250°C for 2 h. The synergist was obtained after cooling. S7: 70g of modified polyethylene, 35g of linear low-density polyethylene, 2g of modified titanium dioxide, 6g of block copolymer, 6g of modified alumina, 5g of methyl acrylate, 2g of diisopropyl peroxide, 3g of antioxidant 1010, and 2g of enhancer were mixed at 180°C for 20min and then compression molded at 125°C. The mixture was then heated to 170°C under a nitrogen atmosphere for cross-linking for 15min, then heated to 190°C for cross-linking for 15min, and finally heated to 205°C for cross-linking for 15min. After cooling, a cross-linked polyethylene material for high-voltage DC cable was obtained.

[0027] Comparative Example 1: Compared with Example 1, this comparative example only replaces the step of "dispersing 30 g of chitosan in 500 mL of 1% acetic acid aqueous solution, and then adding 1 g of hexagonal boron nitride nanosheets and 0.1 g of graphene oxide" added during the preparation of the synergist of S6 with "dispersing 10 g of chitosan in 500 mL of 1% acetic acid aqueous solution, and then adding 0.1 g of hexagonal boron nitride nanosheets and 1 g of graphene oxide". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a cross-linked polyethylene material for a high-voltage DC cable is obtained.

[0028] Comparative Example 2: Compared with Example 1, this comparative example only replaces the "first stage annealing at 100°C for 1h, and then the second stage annealing at 200°C for 2h" added during the preparation of the synergist of S6 with "second stage annealing at 200°C for 3h". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a cross-linked polyethylene material for a high-voltage DC cable is obtained.

[0029] Comparative Example 3: Compared with Example 1, this comparative example only replaces the "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g modified alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist" added in the preparation process of the cross-linked polyethylene material for high-voltage DC cable of S7 with "60g low-density polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g modified alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist". The remaining steps and parameters are the same, and this comparative example will not be repeated again, and finally a cross-linked polyethylene material for high-voltage DC cable is obtained.

[0030] Comparative Example 4: Compared with Example 1, this comparative example only replaces the "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g modified alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist" added in the preparation process of the cross-linked polyethylene material for the high-voltage DC cable of S7 with "90g low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g modified alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist". The remaining steps and parameters are the same, and this comparative example will not be repeated, and finally a cross-linked polyethylene material for a high-voltage DC cable is obtained.

[0031] Comparative Example 5: Compared with Example 1, this comparative example only replaces the "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g modified alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist" added in the preparation process of the cross-linked polyethylene material for the high-voltage DC cable of S7 with "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g nano titanium dioxide, 5g block copolymer, 2g nano alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist". The remaining steps and parameters are the same, and this comparative example will not be repeated, and finally a cross-linked polyethylene material for a high-voltage DC cable is obtained.

[0032] Comparative Example 6: Compared with Example 1, this comparative example only replaces the "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g modified alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist" added in the preparation process of the cross-linked polyethylene material for high-voltage DC cable of S7 with "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 2g modified alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist". The remaining steps and parameters are the same, and this comparative example will not be repeated, and finally a cross-linked polyethylene material for high-voltage DC cable is obtained.

[0033] Comparative Example 7: Compared with Example 1, this comparative example only replaces the "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g nano-alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist" added in the preparation process of the cross-linked polyethylene material for the high-voltage DC cable of S7 with "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g nano-alumina, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist". The remaining steps and parameters are the same, and this comparative example will not be repeated, and finally a cross-linked polyethylene material for a high-voltage DC cable is obtained.

[0034] Comparative Example 8: Compared with Example 1, this comparative example only replaces the "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g nano-alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010, 1g synergist" added in the preparation process of the cross-linked polyethylene material for high-voltage DC cable of S7 with "60g modified polyethylene, 30g linear low-density polyethylene, 0.5g modified titanium dioxide, 5g block copolymer, 2g nano-alumina, 3g methyl acrylate, 1g diisopropyl benzene peroxide, 2g antioxidant 1010". The remaining steps and parameters are the same, and this comparative example will not be repeated, and finally a cross-linked polyethylene material for high-voltage DC cable is obtained.

[0035] Comparative Example 9: Compared with Example 1, this comparative example only replaces the "first heating to 160° C. for cross-linking for 10 min, then heating to 180° C. for cross-linking for 10 min, and finally heating to 195° C. for cross-linking for 10 min" in the preparation process of the cross-linked polyethylene material for the high-voltage DC cable of S7 with "first heating to 160° C. for cross-linking for 10 min, then heating to 180° C. for cross-linking for 10 min, and finally heating to 195° C. for cross-linking for 10 min". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a cross-linked polyethylene material for a high-voltage DC cable is obtained.

[0036] Performance testing: Determination of high temperature resistance: With reference to GB / T 2951.12-2008, "General test methods for insulation and sheathing materials of electric and optical cables - Part 12: General test methods - Thermal aging test," the cross-linked polyethylene materials for high-voltage DC cables prepared in Examples 1 to 3 and Comparative Examples 1 to 9 of the present invention were tested for their aging resistance. The tensile strength (MPa) and elongation at break (%) of the cross-linked polyethylene materials before and after aging at 150°C for 1000 h were recorded. The test results (the temperature of the cross-linked polyethylene material during the test was 25°C) are shown in Table 1.

[0037] Determination of volume resistivity: With reference to GB / T 1410-2006, Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials, the volume resistivity of the cross-linked polyethylene materials for high-voltage DC cables prepared in Examples 1 to 3 and Comparative Examples 1 to 9 of the present invention was measured using a ZC36 megger at a test voltage of 1 kV at 30°C, 90°C, and after aging at 90°C for 1000 h (under these conditions, the testing temperature was 90°C). The test results are shown in Table 1.

[0038] Table 1: Performance test results of Examples 1-3 and Comparative Examples 1-9

[0039] Data Analysis: It can be seen from Table 1 that the cross-linked polyethylene material for high-voltage DC cables prepared in the present invention has more excellent mechanical properties, high temperature resistance and insulation aging resistance.

[0040] This may be due to: (1) The addition of a specific proportion of square boron nitride nanosheets and graphene oxide in the synergist of the present invention can generate a physical cross-linking network and hydrogen bonding and other interaction forces within the cross-linked polyethylene material and form a network skeleton, thereby effectively hindering the crack propagation path and inhibiting the occurrence of phenomena such as strain concentration, carrier migration and electrical tree induction, thereby improving the tensile strength, fracture toughness and impact resistance of the material while also improving the insulation and thermal stability. The bidirectional freeze-gradient annealing process will form an ordered cross-linked structure and a layered multi-arch structure of the synergist, so that the material can disperse stress through the "arch bridge effect", further improving the mechanical properties and thermal stability of the material. The synergist will also work together with diisopropylbenzene peroxide to form a more stable three-dimensional cross-linked network, further improving the thermal stability of the material.

[0041] (2) The present invention improves the polarity and cross-linking degree of low-density polyethylene by grafting and cross-linking with maleic anhydride, and blending it with linear low-density polyethylene in a specific proportion further enhances the interfacial bonding, balances the toughness and strength, crystallinity and uniformity of the cross-linked polyethylene material, and effectively improves the mechanical properties, structural stability, insulation properties and high-temperature stability of the cross-linked polyethylene material.

[0042] (3) The addition of modified alumina in a specific proportion in the present invention can significantly improve the tensile strength, elastic modulus, and wear resistance of the material, form physical crosslinking points, and inhibit chain segment motion. The addition of modified titanium dioxide can improve toughness through interfacial stress transfer, and the two will form a composite reinforcement network within the material, balancing strength and toughness. At the same time, the addition of both can also promote the occurrence of crosslinking reactions, improve the insulation, thermal conductivity, and thermal stability of the material, and inhibit the growth of electrical dendrites, thereby increasing the breakdown field strength.

[0043] (4) The block copolymer of the present invention can be used as an interfacial compatibilizer to improve the compatibility of modified polyethylene and linear low-density polyethylene, reduce phase separation, and enhance the tensile strength and elongation at break of the material. Its polar groups can also produce surface interactions with nanofillers, promote uniform dispersion of fillers, form stronger interfacial bonding, and thus improve the modulus and toughness of the composite material. The block structure of the block copolymer will inhibit the accumulation of space charges and enhance the insulation properties of the material through the synergistic effect of molecular segments. While the block copolymer inhibits the movement of chain segments at high temperatures, its rigid structure will also work together with diisopropylbenzene peroxide to form a thermally stable three-dimensional network, thereby increasing the thermal decomposition temperature and long-term use temperature of the material. The block copolymer will also combine with the layered structure in the synergist to form a "sandwich" interface, further optimizing impedance matching and interfacial polarization loss, and enhancing the material's corona resistance and breakdown strength.

[0044] (5) The specific amount of methyl acrylate added in the present invention can reduce the crystallinity of polyethylene and increase chain segment mobility, thereby improving the material's flexibility and impact strength. Methyl acrylate can synergize with dicumyl peroxide to form a more stable cross-linked structure, increasing the thermal decomposition temperature and long-term heat resistance. The ester group of methyl acrylate can also synergize with antioxidant 1010 to inhibit thermal oxidative degradation, extending the service life of the material at high temperatures.

[0045] (6) The gradient crosslinking of the present invention can avoid violent reactions under a single high temperature, allowing the components to gradually form a synergistic effect, improve the crosslinking structure, inhibit charge accumulation, reduce local stress concentration, internal bubbles and micropore defects, and make the crosslinking more uniform, thereby improving the material's tensile strength, elastic modulus, creep resistance, volume resistivity, breakdown field strength, insulation stability and thermal decomposition temperature. In addition, the nanosheets in the modified alumina, titanium dioxide and synergist will also serve as physical crosslinking points during the crosslinking process, forming a dual reinforcement with the chemical crosslinking network, further improving the mechanical properties and thermal conductivity.

[0046] The above is a detailed description of an embodiment of the present invention. However, the content described is only a preferred embodiment of the present invention and should not be considered to limit the scope of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a cross-linked polyethylene material for a high-voltage DC cable, characterized in that: The following steps are involved: Modified polyethylene, linear low-density polyethylene, modified titanium dioxide, block copolymer, modified aluminum oxide, methyl acrylate, dicumyl peroxide, antioxidant 1010, and synergist are mixed and compression molded, and then gradient cross-linked under a nitrogen atmosphere and cooled to obtain a cross-linked polyethylene material for a high-voltage direct current cable; The preparation method of the synergist is as follows: Chitosan is dispersed in an acetic acid aqueous solution at 10-20°C, and then hexagonal boron nitride nanosheets, graphene oxide and deionized water are added and ultrasonically dispersed. Sodium lauryl sulfate is then added and bidirectionally frozen into shape. After vacuum freeze-drying, gradient annealing is performed in a nitrogen atmosphere, and the synergist is obtained after cooling.

2. The method for preparing a cross-linked polyethylene material for a high-voltage DC cable according to claim 1, wherein: The modified polyethylene, linear low-density polyethylene, modified titanium dioxide, block copolymer, modified aluminum oxide, methyl acrylate, dicumyl peroxide, antioxidant 1010, and synergist are mixed in a ratio of 60-70 g: 30-35 g: 0.5-2 g: 5-6 g: 5-6 g: 3-5 g: 1-2 g: 2-3 g: 1-2 g; The gradient cross-linking comprises first heating to 160-170° C. for cross-linking for 10-15 minutes, then heating to 180-190° C. for cross-linking for 10-15 minutes, and finally heating to 195-205° C. for cross-linking for 10-15 minutes.

3. The method for preparing a cross-linked polyethylene material for a high-voltage DC cable according to claim 1, wherein: The preparation method of the modified polyethylene is as follows: Under a nitrogen atmosphere, low-density polyethylene, maleic anhydride, and dicumyl peroxide are mixed and melt-blended at 180° C. for 20-25 minutes, and then granulated to obtain modified polyethylene; The usage ratio of the low-density polyethylene, maleic anhydride and dicumyl peroxide is 100g:1.5-3g:0.1-0.3g.

4. The method for preparing a cross-linked polyethylene material for a high-voltage DC cable according to claim 1, wherein: The preparation method of the modified titanium dioxide is as follows: The nano-titanium dioxide is dispersed in an ethanol aqueous solution, dopamine hydrochloride is added, ultrasonic treatment is performed, and then centrifugal separation and drying are performed to obtain modified titanium dioxide; The usage ratio of the nano-titanium dioxide, the ethanol aqueous solution and the dopamine hydrochloride is 1-2 g:100 mL:0.05-0.1 g.

5. The method for preparing a cross-linked polyethylene material for a high-voltage DC cable according to claim 1, wherein: The preparation method of the block copolymer is as follows: Step A1: Under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylacetamide were added to 4,4'-oxydiphthalic anhydride in sequence, and the mixture was stirred at 0-5°C for 6-7 hours. Then, acetic anhydride and pyridine were added, and the mixture was heated to 150-180°C and reacted for 5-5.2 hours to obtain a polyimide; Step A2: dissolving polyimide in N,N-dimethylformamide, adding polyethyleneimine and azobisisobutyronitrile, and reacting at 80-90° C. for 7-8 hours to obtain a block copolymer.

6. The method for preparing a cross-linked polyethylene material for a high-voltage DC cable according to claim 5, characterized in that: The ratio of 4,4'-oxydiphthalic anhydride, 4,4'-diaminodiphenyl ether, N,N-dimethylacetamide, acetic anhydride, and pyridine in step A1 is 27-31 g: 17.6-20 g: 200 mL: 15-17 g: 10-11.4 g; The usage ratio of the polyimide, N,N-dimethylformamide, polyethyleneimine, and azobisisobutyronitrile in step A2 is 40-45 g:150 mL:5-5.7 g:0.5-0.57 g.

7. The method for preparing a cross-linked polyethylene material for a high-voltage DC cable according to claim 1, wherein: The preparation method of the modified alumina is as follows: The silane coupling agent KH550 and ethanol are mixed evenly, and then nano-alumina is added and ultrasonically treated at 55-60° C. for 2-3 hours, and then centrifuged and dried to obtain modified alumina.

8. The method for preparing a cross-linked polyethylene material for a high-voltage DC cable according to claim 7, wherein: The usage ratio of the silane coupling agent KH550, ethanol and nano-alumina is 0.04-0.18 g:100 mL:2-6 g.

9. The method for preparing a cross-linked polyethylene material for a high-voltage DC cable according to claim 1, wherein: The chitosan, acetic acid aqueous solution, hexagonal boron nitride nanosheets, graphene oxide, deionized water, and sodium lauryl sulfate are used in a ratio of 30-50 g: 500 mL: 1-2 g: 0.1-0.5 g: 500-600 mL: 0.05-0.1 g; The gradient annealing is performed at 100° C. for 1 h in the first stage annealing, and then at 200-250° C. for 2 h in the second stage annealing.

10. A cross-linked polyethylene material for high-voltage DC cables, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-oxygen-resistance polymer nano-composite film and preparation method thereof

    CN109880267A

  • Crosslinked polyethylene cable insulating material and preparation method thereof

    CN110791003A

  • Low-filling high-thermal-conductivity natural rubber nano composite material and preparation method thereof

    CN116496557A

  • Preparation method of antibacterial self-cleaning moisture-proof and mildew-proof wood-plastic wallboard

    CN118460009A

  • Dynamic polymer having hybridized crosslinked structure and applications thereof

    WO2018137506A1